Financial literacy mediates the effect between verbal intelligence and financial anxiety. (March 2023) - Gignac, Gilles E.; Gerrans, Paul; Andersen, Camilla B.
Abstract: Financial anxiety can impact financial decision-making negatively. Theoretically, knowledge is considered to help mitigate stress in making decisions. However, the empirical results are inconsistent with respect to the association between financial literacy (knowledge of financial terms and concepts) and financial anxiety, perhaps because of the employment of limited psychometric measures. Furthermore, cognitive intelligence and financial literacy inter-correlate positively, suggesting that any effect between financial literacy and financial anxiety may be accounted for by intelligence, a construct known to facilitate problem solving. Consequently, measures of verbal intelligence (vocabulary and verbal reasoning), financial literacy, and financial anxiety were administered to a sample of 553 adults. Vocabulary and verbal reasoning were found to associate positively with financial literacy, however, only vocabulary associated with financial literacy uniquely. Furthermore, while vocabulary and financial literacy correlated negatively with financial anxiety, the effect between vocabulary and financial anxiety was fully mediated by financial literacy, controlling for education and age. We conclude that financial literacy appears to have a direct effect onto financial anxiety, independently of the effects of verbal intelligence, formal education, and age, supporting the potential usefulness of financial literacy training.